Ecosol Performance Measurement Information System - Esteban Regino, Edna Margarita; Rua Castañeda, Sohely; García Cabralez, María Paula; Álvarez Lambertinez, Sebastián Andrés (Cooperativismo & Desarrollo, 2024)
The research results shown correspond to an intermediate stage in the design of an information system capable of measuring the impact of social and solidarity economy on local development and territorial ecosystems. In this intermediate stage, a systematic literature review study on performance evaluation tools or information systems in the solidarity sector was conducted, following the three-stage model: planification, execution and data analysis, proposed in Kitchenham and Charters (2007). The goal of this review is to ensure that the information system to be designed takes into account the progress made in the area and fills the information gaps required to evaluate the contribution made by the solidarity economy to the achievement of the sustainable development objectives. The applied methodology included a document quality assessment process, guided by six questions and three evaluation criteria. The results obtained highlight the identification of guiding principles for the design: simplicity of data accessibility, dynamic balance in the dimensions and suitability for practical use. Likewise, the companies in the solidarity sector expect the impact measurement should articulate diagnoses and planning strategies, as well as the results of monitoring and control of social and business solidarity balance.